2009
DOI: 10.1097/ncc.0b013e31819deab0
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Risk Perception and Lifestyle Behaviors Among White and Black Women With a Family History of the Disease

Abstract: Little is known about relationships between a positive family history of breast cancer, perception of risk, and lifestyle behaviors. This qualitative study explored factors involved in formulation of perceived breast cancer risk and the association between risk perception and lifestyle behaviors in white and black women with a family history of breast cancer. Eligible participants were North Carolina residents in the Sister Study, a nationwide study of environmental and genetic risk factors for breast cancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 30 publications
6
50
0
Order By: Relevance
“…Similar to previous research [24,26,38], our study identified that risk perception impacts on access and utilisation of the NHSBSP. Although our participants acknowledged genetic/ hereditary and lifestyle as risk factors for breast cancer, they did not perceive themselves as being at risk of developing the disease and felt that being symptom-free meant that they did not need to attend breast screening.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Similar to previous research [24,26,38], our study identified that risk perception impacts on access and utilisation of the NHSBSP. Although our participants acknowledged genetic/ hereditary and lifestyle as risk factors for breast cancer, they did not perceive themselves as being at risk of developing the disease and felt that being symptom-free meant that they did not need to attend breast screening.…”
Section: Discussionsupporting
confidence: 70%
“…Research has also reported that religion and culture influence patients' health behaviour in terms of the perceived benefit of engaging in recommended disease prevention activities choice of treatment options and delays in help-seeking [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is currently estimated that approximately 5% of breast cancer cases can be attributed to alcohol (44), very few women may be aware of the association between alcohol and breast cancer (45). In light of the increasing frequency of binge drinking in the United States (1), the impact of binge drinking on health may increase and will continue to be a topic of concern.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, one study found a 17.6% increase in mammographic density among women using HRT [41]. One qualitative study of sisters of women diagnosed with breast cancer found that many women identified HRT as a risk factor and several stopped their therapy after their sister's diagnosis, as it was viewed as a modifiable risk factor [43]. However, HRT may not be a significant factor in triple-negative breast cancers in African American women, as it is more commonly used among white Americans and postmenopausal women [11].…”
Section: Hormonal Factorsmentioning
confidence: 99%